(untitled) (Research, Society and Development, 2020)
This study aims to analyze the process by which public policy relating to Physical Education Teacher Education in Brazil is developed, highlighting both the most important advances and the issues that still need to be better understood and evolved. To that end, from an interpretative research approach, we analyzed documents related to several laws and guidelines of Brazilian public policy. The results focus on the relation between Physical Education in Brazil and the field of public policies in a historical analysis and its intersection with a sociological perspective. This article concludes that although the field of Physical Education has achieved greater social importance in public policies, there are still several challenges that it must overcome to achieve social legitimacy. Further studies in this approach are therefore necessary to shed light on what is not apparent but is nevertheless part of "how the game is played".